Drug law enforcement in India - Singh, K.P. (2000)
India's narcotic problem is very complex because of its proximity to the two major opium producing regions - the Golden Crescent on the west and the Golden Triangle on the east. Further, being a licit producer of opium for medicinal and research purposes, there always are chances of pilferage from the licit to elicit channel. Growing liberalisation of economy and lessening of trade barriers have added a new dimension to this problem with the result we face an ever-increasing danger of exploitation of normal trade channels for narcotics trafficking. A number of central and state agencies are involved in the implementation of NDPS Act and there is lack of proper co-ordination among them. This article deals with practical difficulties encountered in effective enforcement of NDPS Act. - Reproduced
Keywords: Drug abuse - India; Drug policy - India; Drug policy